2019
DOI: 10.1002/gj.3554
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology and geochemistry of the Late Devonian–Early Carboniferous volcanic rocks in Aksu River area, western end of the East Kunlun Orogen

Abstract: We present LA‐ICP‐MS zircon U–Pb dating, geochemical data for the Late Devonian–Early Carboniferous volcanic rocks in the Aksu River area, western end of the East Kunlun Orogen, with an aim to constrain the ages, petrogenesis, and tectonic setting of volcanic rocks and to comprehend the Late Devonian–Early Carboniferous tectonic evolution of the north branch of the Paleo‐Tethys Ocean. The Late Devonian–Early Carboniferous volcanic rocks are mostly composed of andesite and rhyolite. The new U–Pb ages show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
(130 reference statements)
0
5
0
Order By: Relevance
“…The granites are part of a tripartite association consisting of inboard S‐type granite, outboard oceanic arc, and intervening, turbidite‐filled back‐arc basin (Collins & Richards, ). Xu et al () reported 344–362 Ma arc volcanic rocks from the western part of the EKO and suggested the onset of the northward subduction of a north branch of the Paleo‐Tethys oceanic crust occurred earlier than 362 Ma. Jia, Meng, and Feng () studied the Wenquan Carboniferous ophiolites and suggested the existed of Carboniferous oceanic basin in the Central East Kunlun Fault zone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The granites are part of a tripartite association consisting of inboard S‐type granite, outboard oceanic arc, and intervening, turbidite‐filled back‐arc basin (Collins & Richards, ). Xu et al () reported 344–362 Ma arc volcanic rocks from the western part of the EKO and suggested the onset of the northward subduction of a north branch of the Paleo‐Tethys oceanic crust occurred earlier than 362 Ma. Jia, Meng, and Feng () studied the Wenquan Carboniferous ophiolites and suggested the existed of Carboniferous oceanic basin in the Central East Kunlun Fault zone.…”
Section: Discussionmentioning
confidence: 99%
“…During the late Devonian–early Carboniferous, the northward subduction of the Kunlun oceanic crust led to the formation of the Tuokuzidaban Group arc volcanic rocks (e.g., Wu et al, ; Wu, Zuza, et al, ; Xu et al, ). The Jianxiashan S‐type granites herald the slab retreat phase because the initial burst of mantle‐derived arc magmatism weakens the lithosphere along the arc locus (Figure ), which becomes the site for crustal extension as rollback progresses (Collins & Richards, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The granite‐MME associations have been widely documented in many complexes from Middle Permian to Late Triassic: the Naomuhun granodiorites and their MMEs (Xiong et al, 2012), the Qianwadaqiao granodiorites and their MMEs (G. C. Chen, Pei, Li, Li, Pei, et al, 2018), the Qushi'ang granodiorites and their MMEs (G. C. Chen, Pei, Li, Li, Liu, Chen, et al, 2017), the Harizha granodiorites and their MMEs (Xin et al, 2019), the Saishitang granodiorites and their MMEs (J. Y. Zhang, Yang, et al, 2017), and the Xiangride porphyritic granodiorites and their MMEs (Xiong, Ma, Zhang, Liu, & Jiang, 2014). The EKOB in the Qinghai‐Tibetan Plateau is considered to undergo multi‐stages of tectonic‐magmatic evolution (Y. X. Chen, Pei, Li, Li, Liu, & Wang, 2017; Y. P. Dong et al, 2018; Du et al, 2017; J. J. Kong, Niu, He, Zhang, & Shao, 2020; Z. C. Li, Pei, et al, 2017; Y. G. Liu et al, 2018, 2019; X. Xu et al, 2020; Z. W. Zhang et al, 2018; M. J. Zhang et al, 2021). The evolutionary history of the Palaeo‐Tethys within the EKOB has attracted considerable attention over the past decades (Y. P. Dong et al, 2018; Gao & Sun, 2021; Hu et al, 2016; Huang et al, 2014; J. J. Kong et al, 2020; H. L. Kong et al, 2021; Y. Y. Liang, Xia, Ma, Zhao, & Guo, 2020; Richards, 2015; Shao et al, 2017; Song et al, 2020; Tian et al, 2021; J. Y. Zhang, Ma, Xiong, & Liu, 2012; Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%